RE-ASSESSING THE JURISPRUDENCE OF THE EUROPEAN COURT OF HUMAN RIGHTS ON POLICE INTERROGATION - CASE OF IBRAHIM AND OTHERS V. THE UNITED KINGDOM (EU and comparative law issues and challenges series (ECLIC), 2018)
The article gives an analysis of the judgment of the Grand Chamber of the European Court of Human Rights in the case Ibrahim and others v. the United Kingdom. The analysis is put in the context of standards that the Court established in its Salduz judgment and further developed in its post-Salduz jurisprudence. The author presents and analysis the way in which the Court interpreted the Salduz standards in the instant case, focusing on the standard of “compelling reasons” and the relationship between the use of the statements given in the absence of a lawyer and the fairness of the proceedings as a whole. The central part of the article is dedicated to the critique of the way in which the Court applied these standards to the circumstances of this particular case. The author offers counter-arguments to Court’s findings both in relation to the question whether compelling reasons to restrict the right of access to a lawyer existed in this case, as well as the question of the fairness of the trial as a whole.